The board gender composition and cost of debt: empirical evidence from Jordan - Mansour, Marwan; Al Zobi, Mo'taz; Saleh, Mohammed W. A.; Al‐Nohood, Saddam; Marei, Ahmad (Wiley, 2024)
The present research aims to examine the influences of board gender composition on debt costs and its significance to Jordanian creditors: mainly banks, using agency and resource dependence theories. A sample of 113 non‐financial Jordanian firms listed on the Amman Stock Exchange (ASE) from 2010 to 2019 was utilised to explore the impact of board gender on the cost of debt financing through panel regression analysis. To tackle endogeneity concerns, we employ a two‐step system generalised method of moments estimator. The findings discovered that more female directors on firm boards generated economic benefits for non‐financial sectors, which achieved an average 0.75% cut‐off interest rate incurred by lenders compared to the counterparts with fewer female directors. Our findings are still robust to endogeneity concerns. The findings offered valuable insights for academics, shareholders, firms, and regulators. Shareholders are required to provide more pressure on firms to enhance gender equality. Firms should adjust board gender composition via the inclusion of more female directors while regulators should develop guidelines, such as a minimum female quota in promoting more females to the board. The finding generalisability is limited to developing markets with similar settings. This study bridged a vital gap in the governance literature on the nexus between board gender composition and debt costs in Jordanian contexts where no minimum gender quota exists.